Peningkatan Keterampilan Kepemimpinan Pelaku UMKM di Nipah Panjang, Tanjung Jabung Timur - Sry Rosita; Idham Khalik; Husni Hasbullah; Suswita Roza; Feny Tialonawarmi (Jurnal Surya Masyarakat, 2025)
Activity Community service focuses on improving skills, leadership, Micro, Small, and Medium Enterprises (MSMEs) in Nipah Panjang, East Tanjung Jabung, Jambi Province. The majority of residents are professionals in the trades and fisheries, and the presence of 92 small businesses in the industry has become potentially important in expanding the local economy. Although MSMEs play a significant role in the economy's growth, many entrepreneurs face challenges due to weak skills and leadership, which affects their management and business sustainability. Through method training and mentoring, research, this program introduces the concept of digging potential and developing leadership skills. This program consists of four stages: introduction to skills, leadership training, in-depth training, and mentoring for sustainability. The focus of the main training covers ability communication, decision-making, and management team development, as well as the implementation of innovative strategies in management efforts. The results of the activity are expected to strengthen the leadership foundation of UMKM actors, enabling them to compete in increasingly complex market conditions. With improved leadership skills, expected MSME actors in Nipah Panjang can be more independent, innovative, and empowered, contributing to a more competitive local economy. Community service makes an important contribution to the development of MSMEs by improving the capacity source, particularly human capital, at the local level.